The need for evidence-based strategies and tools for onchocerciasis elimination in Africa - Yankum Dadzie; Uche V. Amazigo; Boakye A. Boatin; Azodoga Sékétéli (BMC, 2019)
Abstract In a recent article we discussed the feasibility of onchocerciasis elimination in Africa by 2025. We expressed concern that elimination may be impeded by failure to build on the lessons learned in the African onchocerciasis control programmes and the introduction of strategies and tools from the Americas. Richards et al. and Cupp et al. wrote to refute our concern and described recent achievements with stopping treatment in some areas. In this response, we discuss their arguments which did not convince us. We point out several scientific flaws in the American conceptual framework of elimination which has led to longer periods of treatment than necessary, and in the use of an arbitrary threshold for stopping treatment. We show that recent achievements fall significantly short of what would be needed to achieve onchocerciasis elimination by 2025. We conclude our response by advocating for a more objective and inclusive debate on strategies and tools for onchocerciasis elimination.